Improving Students' Fine Motor Skills Through Cow Milking Simulation Training at Bauzan Jaya PAUD - Listas Kuroainy; Yuliana Yuliana; Ahmad Farihin (Bale Pengabdian: Journal Of Community Service (BPJCS), 2026)
Limited fine motor skills represent a significant challenge for students at Bauzan Jaya Early Childhood Education (PAUD), where the daily learning process does not optimally facilitate the development of these essential skills. This problem is rooted in the lack of variety in interesting and relevant learning methods and media, resulting in suboptimal stimulation of students' fine motor skills. The main objective of this community service activity is to improve students' fine motor skills through the implementation of a cow milking simulation training method. The implementation method of this activity is carried out through three main stages: (1) observation and needs analysis to identify students' initial level of fine motor skills and the availability of resources; (2) designing and creating safe and attractive cow milking simulation media; and (3) implementing practical training in cow milking simulations involving squeezing, pinching, and pressing activities. The results demonstrate a significant increase in students' fine motor skills, particularly in aspects of eye-hand coordination, finger strength, and dexterity in grasping and releasing objects. The activity also yielded the diversification of innovative, effective, and enjoyable learning methods, which directly contribute to increasing students' readiness to enter the next level of education. This activity successfully provided an easily adaptable and sustainable alternative learning medium for Bauzan Jaya PAUD teachers to use.